Uso de barreiras físicas em voçoroca e seus efeitos na retenção de sedimentos : um estudo de caso - Pereira Junior, Renato Alves (2013)
The study area is located in Uberlandia - MG, in the Experimental Farm of Glory, becoming an integral part of Triangulo Mineiro, located in the western portion of the state of Minas Gerais under morphostructural in Paraná Sedimentary Basin, as part of \" Morphoclimatic Domain of Cerrados \"where are found the different vegetation types that comprise the savannahs in Brazil. Among the soil more susceptible to erosion highlight the Entisols, Inceptisols, Ultisols and sandy loam Oxisols, which occur in the Cerrado region with major Latossolo to medium texture. In this context the object of study is the main channel of a gully with over 30 years of existence, it has 250 meters of extension with a maximum depth of 8 meters. This area is highly degraded by human action, marked the beginning of their exploitation by the removal of natural vegetation for pasture formation and later with exploration activity gravel. With the development of these activities and the lack of adequate management and soil conservation, soil erosion established in the area. The gully erosion processes are well developed work processes where surface and subsurface, being difficult to stabilize. The genesis of formation of gullies can arise from several causes, and can highlight the concentrated runoff, the evolution of gullies and subsidence of the ground surface due to headward erosion. Referring to these erosive processes can be applied physical, biological and soil, in order to prevent or reduce the effects of degradation. Measures physical or mechanical practices are those that make use of artificial structures in order to reduce the flow of surface water flow, intercepting it and making this happen so will minimize the loss of soil aggregates. In this context, the objective is to adapt the technical barrier palisade applied by Machado et al (2006 ) to contain sediment in a gully, where the presence of water is constant throughout the year. The technique seeks to elevate the level of base and contain sediment within the gully through adaptations made by the technical barrier of palisades. 5 stockade barriers were constructed between July 05 and September 15, 2011 , staying in monitoring these dates through the month of December 2012. 3 these barrier were constructed of wood and 2 barrier of bamboo, to identify whether there is difference in resistance between these materials. For evaluation of the proposed measures were monitored rainfall data, flow and sediment dissolved in water seeping through gully, from July 2010 until December 2012, one year before the application of the technique, and a half years after the construction of barriers. After installation of the barriers has happened ruptions of these barriers, what to made necessary to further adapt the technique, however got positive results with sediment retention until the top of one of the barriers in the study period. The results show the effectiveness of the barriers built through precipitation data, flow, sediment dispersed in water and sediment accumulated in the barriers .